Interaction of tubulin with ribose-modified analogs of GTP and GDP: evidence for two mutually exclusive exchangeable nucleotide binding sites. - Hamel, E (1981)
Interactions of tubulin with a number of guanine nucleotides modified at the 2' and 3' ribose hydroxyls were examined. Deoxy analogs of GTP were equal or superior to GTP in supporting tubulin polymerization, but analogs bearing either methyl or phosphate groups on the hydroxyls had significantly reduced ability to support polymerization. These substituted GTP analogs were hydrolyzed at the 5'-gamma-phosphate position, although less rapidly than GTP, at rates exceeding those of polymerization. GTP hydrolysis, however, was closely coupled to polymerization. Moreover, the partially active GTP analogs were not effective inhibitors of GTP-dependent polymerization. These data indicate that the substituted GTP analogs have reduced affinity for tubulin at the exchangeable site because of steric factors. No deoxy or substituted GDP analog was as effective as GDP itself in inhibiting GTP-supported tubulin polymerization. Furthermore, there was no apparent relationship between the ability of nucleoside 5'-triphosphates to support polymerization and that of nucleoside 5'-diphosphates to inhibit the reaction. These findings suggest that GTP and GDP may actually bind to different, mutually exclusive sites rather than to a single exchangeable site.